A Petrel for the Digital Storm - Rajagopal, Lakshmi R; Provodnikova, Anna; Soans, Frank (Global journal of Business and Integral Security, 2026)
The world we live in today is fascinating, we are at the cusp of the fourth and fifth industrial revolution. It took us almost three centuries to get here since the first industrial revolution, the good part is that we will not have to wait for an equal period to experience the subsequent industrial revolutions. The pace and intensity of change is unprecedented and gives one the feeling of being in a sci-fi movie. Vectors shaping the future of work are complex, nuanced and multi-dimensional requiring us to adopt varied strategies so as to thrive in the current order. It requires us to transcend into higher maturity levels of change navigation continuum - to become change architects for our personal selves. Being a change architect would amplify the vector qualities required to sense-make the future. It would help optimise the efforts and energy required to thrive in the future through materiality, intentionality and directionality. This paper takes inspiration from nature, our biggest teacher on how humans can become better change architects to thrive in the future.